Suppressing Effect of Baclofen on Multiple Alcohol-Related Behaviors in Laboratory Animals - Colombo, Giancarlo; Gessa, Gian Luigi (Frontiers in Psychiatry, 2018)
This paper summarizes the several lines of experimental evidence demonstrating the ability of the prototypic GABAB receptor agonist, baclofen, to suppress multiple alcohol-related behaviors in laboratory rodents and non-human primates exposed to validated experimental models of alcohol use disorder (AUD). Specifically, treatment with baclofen has repeatedly been reported to suppress alcohol-induced locomotor stimulation, alcohol drinking (including binge- and relapse-like drinking), operant oral alcohol self-administration, alcohol seeking, and reinstatement of alcohol seeking in rats and mice. Treatment with baclofen also reduced operant oral alcohol self-administration in baboons. Several of these effects appear to be mediated by GABAB receptors located in the ventral tegmental area, a key area of the brain “reward” system. The relatively modest separation between the “desired” pharmacological effects and “unwanted” sedative effects appears to be the major drawback of the preclinical, anti-alcohol profile of baclofen. Collectively, these data underline the role of the GABAB receptor in the mediation of several alcohol-related behaviors. These data possess remarkable translational value, as most of the above effects of baclofen have ultimately been reproduced in AUD patients.